Feminist Materialism and Covid-19: The Agential Activation of Everyday Objects. Issue 1 (2nd January 2021) - Sikka, Tina
ABSTRACT: This article takes up and make the case for the study of Covid-19 through the lens of feminist new materialism and asks how this approach might draw out perspectives and insights overlooked by other frameworks. I begin with a brief introduction to Covid-19 followed by an analysis of the virus through the lens of feminist new materialism by drawing on the work of Karan Barad (2003), Rosi Braidoitti (2011), and Jane Bennett (2004). I contend that the interconnected frameworks articulated by each of these theorists provides the basis for a more robust understanding of the viral non-human (Covid 19) and everyday objects (the toilet roll and medical masks) whose agentic power is embedded in larger assemblages of natureculture. This kind of analysis is urgent in light of our current media-saturated, interconnected, highly politicized, and expert-adverse environment.